2003
DOI: 10.1093/hmg/ddg246
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of human promoter polymorphisms

Abstract: The potential importance of gene regulation in disease susceptibility and other inherited phenotypes has been underlined by the observation that the human genome contains fewer protein coding genes than expected. Promoter sequences are potential sources of polymorphism affecting gene expression, although to date there are no large-scale systematic studies that have determined how frequently such variants occur. We have used denaturing high performance liquid chromatography to screen the first 500 bp of the 5' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(134 citation statements)
references
References 25 publications
12
121
0
1
Order By: Relevance
“…Almost one-third of promoter variants may alter gene expression and result in phenotypic variation (30). The effects of different alleles (T versus G) in the SNP rs1617640 of the EPO promoter on its expression are consistent with this notion.…”
Section: Discussionmentioning
confidence: 57%
“…Almost one-third of promoter variants may alter gene expression and result in phenotypic variation (30). The effects of different alleles (T versus G) in the SNP rs1617640 of the EPO promoter on its expression are consistent with this notion.…”
Section: Discussionmentioning
confidence: 57%
“…Typically, cis-acting eQTL are considered to include SNPs that are within 100 kb upstream and downstream of the gene that is affected by that eQTL. On the basis of earlier work involving human genes with promoter polymorphisms, it has been estimated that a sizable fraction of cisvariants (about one-third of the SNPs in promoters) may alter gene expression (Hoogendoorn et al, 2003;Buckland, 2004). One study recently reported on the investigation of cis-regulatory variations in 3 0 -UTRs for a set of genes showing cis-acting regulation in a panel of mouse recombinant congenic strains (Lee et al, 2006).…”
Section: S Ponsuksili Et Almentioning
confidence: 99%
“…Particularly, the promoter region of genes contains polymorphisms and such polymorphisms have been shown to contain a large amount of genetic variation [33]. Gene polymorphisms associated with DOR are discussed in Table 1.…”
Section: Fragile X Mental Retardation 1 (Fmr1)mentioning
confidence: 99%